POLITICAL WILL PEMERINTAH DALAM MENGURUS JALAN KABUPATEN (STUDI KASUS DI DESA LEMBAH DUSUN GADING KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU TAHUN 2022-2023) - Andini, Annisa Shofia; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The district or city government has the authority to administer roads, including the administration of district or city roads, which includes the regulation, guidance, construction and supervision of district or city roads. Landslides are a natural phenomenon that occurs due to erosion of water flow on river beds and banks which has been going on since 2021 and until now there has been no effective response by the government. This research aims to determine the government's political will in managing district roads in Lembah Dusun Gading Village, Pasir Penyu Subdistrict, Indragiri Hulu District in 2022-2023. This research is a descriptive study with a qualitative approach. The types of data used are primary and secondary data. Primary data is obtained directly from informants, while secondary data is supportive data that strengthens the primary data. Data collection techniques include interviews and documentation. This study uses Brinkerhoff's political will theory, which encompasses government initiative, government priority, mobilization of support from various parties, and sustainability of efforts. The results of this study indicate that the government's political will of the government in managing district roads in Lembah Dusun Gading Village has not been well implemented. Although the government has initiated the construction of road relocation or alternative roads, they have not formulated effective long-term policies for landslide mitigation. This is due to the large budget required for such mitigation and the lack of commitment from the relevant agencies as well as the insufficient involvement of the community. Keywords: Political Will, Government, District Road